Dermatofibroma in a black tattoo: report of a case - Maraya de Jesus Semblano Bittencourt; Mario Fernando Ribeiro de Miranda; Amanda Magno de Parijos; Leticia Brito Mesquita; Diana Mendes da Fonseca; Diego Augusto Aiezza Jambo (Sociedade Brasileira de Dermatologia, 2013)
Tattooing has been associated with a variety of complications including inflammatory and granulomatous reactions, transmission of infections, and neoplasms. We report a case of a 24-year-old male who presented with a 2-month history of an erythematous nodule involving a newly made tattoo on the right leg. An excisional biopsy was performed and the histopathological evaluation was consistent with dermatofibroma. Only three cases of dermatofibroma associated with tatooing were reported in litetature. We report an additional case and review the literature regarding cutaneous reactions to tattoos.